2006
DOI: 10.1016/j.virol.2005.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Complete nucleotide sequence and genome analysis of bacteriophage BFK20 — A lytic phage of the industrial producer Brevibacterium flavum

Abstract: The entire double-stranded DNA genome of bacteriophage BFK20, a lytic phage of the Brevibacterium flavum CCM 251--industrial producer of L-lysine--was sequenced and analyzed. It consists of 42,968 base pairs with an overall molar G + C content of 56.2%. Fifty-five potential open reading frames were identified and annotated using various bioinformatics tools. Clusters of functionally related putative genes were defined (structural, lytic, replication and regulatory). To verify the annotation of structural prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 82 publications
1
25
0
Order By: Relevance
“…Using this equation, the length of the tails in PH15 and CNPH82 corresponds to 155 nm (TMP, 1,034 amino acids), which correlates well with our estimation from the electron micrographs. Similar calculations of tail length based on TMP size have also been made for phages that are unrelated to (11,44,62,81,82).…”
Section: Resultsmentioning
confidence: 82%
“…Using this equation, the length of the tails in PH15 and CNPH82 corresponds to 155 nm (TMP, 1,034 amino acids), which correlates well with our estimation from the electron micrographs. Similar calculations of tail length based on TMP size have also been made for phages that are unrelated to (11,44,62,81,82).…”
Section: Resultsmentioning
confidence: 82%
“…Subsequently, it could be shown that this is due to an induction of the CGP3 prophage in C. glutamicum. Upon induction, the CGP3 DNA becomes excised from the genome and exists as a doublestranded DNA phage with cohesive ends, like the majority of other known corynephages (2,22,24,30). Until now, the CGP3 prophage DNA (ϳ187 kbp) was supposed to exist exclusively as a genomic island integrated into the C. glutamicum genome.…”
Section: Discussionmentioning
confidence: 99%
“…The 36.5-kb prophage genome has a GϩC content of 52.2% and encodes 43 predicted proteins. Its closest sequence matches at the amino acid level were with deduced structural proteins of the lytic phage BFK20 of "Brevibacterium flavum" (52). However, its genome organization resembles that of phages infecting low-GϩC gram-positive bacteria, and several of its proteins show weak sequence similarities with these phages (50).…”
Section: Prophage-like Element In the Genome Of C Diphtheriaementioning
confidence: 99%
“…The SSIs are loaded mainly with transposable elements and genes of unknown function, although several enzymes and proteins of a diverse functional context are also encoded on the islands (415,416). SSI-8 includes a gene region with deduced amino acid sequence similarity to proteins of the lytic corynephage BFK20 from the industrial amino acid producer "Brevibacterium flavum" (52). By means of a precise genome excision method based on the Cre/loxP recombination system, the 11 SSIs were individually deleted from the C. glutamicum R genome (415,416).…”
Section: Corynebacterium Comparative Genome Analysismentioning
confidence: 99%
See 1 more Smart Citation